Taxonomy and morphology of Phacidiella kunmingensis sp. nov. (Stictidaceae) from southwest China - Wei, De-Ping; Gentekaki, Eleni; Wanasinghe, Dhanushka N.; Hyde, Kevin D.; To-Anun, Chaiwat; Cheewangkoon, Ratchadawan (Phytotaxa, 2022)
Stictidaceae was formally introduced as a group of saprotrophic discomycetes. The majority of Stictidaceae species are documented and described from Europe, North America and South America. In contrast, knowledge on stictidaceous fungi in African and Asian continents is lacking. In this study, a novel saprophytic species, Phacidiella kunmingensis sp. nov. was discovered from dead woody twigs in Yunnan Province, China. The new species was described based on its sexual morph, which is characterized by apothecial ascomata, yellow disc, white-pruinose margin, crystalline exciple, filiform paraphyses, cylindrical asci and filiform, multiseptate, non-disarticulating ascospores. Its taxonomic position was inferred using phylogenetic analyses of combined LSU, ITS, mtSSU and rpb2 sequence and further confirmed by morphological studies.